Analysis the Effect of Activated Natural Zeolites for Fe Metal Adsorption - Fadliah, Fadliah; Palit, Christin; Pratiwi, Reno; Aryanto, Reza; Putri, Tri Widayati (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Zeolite, as an adsorbent, can be improved by a chemical activation process. In this study, zeolite was activated using the acid activation method by soaking natural zeolite with HCl and HF, and the activated zeolite was then used to adsorb Fe metal. Zeolite was characterized using SEM and XRD, and the adsorption capacity of the zeolite was analyzed using AAS. The results of SEM analysis show that zeolite after activation has a more significant number of pores than zeolite before activation. The results of XRD analysis show that zeolite that has been activated has a higher content of quartz (SiO2) and clinoptilolite than zeolite that has not been activated. The results of the zeolite adsorption capacity and efficiency test on Fe metal showed that the most excellent adsorption capacity was when the contact time was 60 minutes, with adsorption capacity and adsorption efficiency values of 3.2403 mg/g and 97.21%.